Cascading style sheets : the definitive guide - Meyer, Eric A. (O'Reilly, 2004)
Simply put, Cascading Style Sheets (CSS) is a way to separate a document's structure from its presentation. The benefits of this can be quite profound: CSS allows a much richer document appearance than HTML; CSS saves time--you can create or change the appearance of an entire document in just one place; and its compact file size makes web pages load quickly. Eric Meyer, a member of the CSS&FP Working Group and an internationally known expert on HTML and CSS, tackles the subject with passion and delivers a comprehensive and thorough update to his groundbreaking book. All readers will benefit from both the depth and breadth of his experience and his clear and honest style. Cascading Style Sheets: The Definitive Guide , 2nd Edition is a thorough review of all aspects of CSS2.1 and a comprehensive guide to CSS implementation. The book includes new content on positioning, lists and generated content, table layout, user interface, paged media, and more. It explores in detail each individual CSS property and how it interacts with other properties, and shows how to avoid common mistakes in interpretation. If you're ready to take the next step with your HTML coding and incorporate CSS or are already a CSS code warrior, you'll find Cascading Style Sheets: The Definitive Guide , 2nd Edition is the book you've been craving.